Validity and reproducibility of a Spanish dietary history. - Pilar Guallar-Castillón; Jon Sagardui-Villamor; Teresa Balboa-Castillo; Aleix Sala-Vila; Maria José Ariza Astolfi; Maria Dolores Sarrión Pelous; Luz María León-Muñoz; Auxiliadora Graciani; Martín Laclaustra; Cristina Benito; José Ramón Banegas; Fernando Rodríguez Artalejo (PLoS ONE, 2014)
To assess the validity and reproducibility of food and nutrient intake estimated with the electronic diet history of ENRICA (DH-E), which collects information on numerous aspects of the Spanish diet.The validity of food and nutrient intake was estimated using Pearson correlation coefficients between the DH-E and the mean of seven 24-hour recalls collected every 2 months over the previous year. The reproducibility was estimated using intraclass correlation coefficients between two DH-E made one year apart.The correlations coefficients between the DH-E and the mean of seven 24-hour recalls for the main food groups were cereals (r = 0.66), meat (r = 0.66), fish (r = 0.42), vegetables (r = 0.62) and fruits (r = 0.44). The mean correlation coefficient for all 15 food groups considered was 0.53. The correlations for macronutrients were: energy (r = 0.76), proteins (r= 0.58), lipids (r = 0.73), saturated fat (r = 0.73), monounsaturated fat (r = 0.59), polyunsaturated fat (r = 0.57), and carbohydrates (r = 0.66). The mean correlation coefficient for all 41 nutrients studied was 0.55. The intraclass correlation coefficient between the two DH-E was greater than 0.40 for most foods and nutrients.The DH-E shows good validity and reproducibility for estimating usual intake of foods and nutrients.